Problem Gambling Transmission. An Eight-wave Longitudinal Study on Problem Gambling Among Affected Others - Kauppila, Emmi; Hautamäki, Sari; Savolainen, Iina; Castrén, Sari; Velleman, Richard; Oksanen, Atte (Springer Science and Business Media LLC, 2026)
There is growing recognition that those close to someone with problem gambling experience stress and strain. Research suggests they may also be at risk of developing gambling problems themselves, but this remains an underexplored area. The present study examined how exposure to problem gambling within family or friend networks relates to affected others’ own gambling, and whether strong social connections reduce this risk. Using an eight-wave longitudinal dataset (N = 1530) with hybrid multilevel regression modeling, we analyzed within-person and between-person effects of exposure to a family member’s or friend’s problem gambling on affected others’ own gambling. We further examined the protective role of social connectedness to family and friends. Gambling problems were assessed with the Problem Gambling Severity Index (PGSI) and social relationships with the Social and Emotional Loneliness Scale for Adults (SELSA). Results indicated that individuals were more likely to develop problem gambling when they reported that a family member or a friend had gambling problems. Strong family relationships buffered against this risk, whereas friendships did not provide the same protection. These findings suggest that social relationships play an important role in shaping problem gambling among affected others and highlight the need to consider family and peer contexts in prevention and intervention strategies.